Teaching vaccine development in schools: Learnings from a survey and curriculum design for a course - Ghosh, Aishani; Lalsare, Arav; Chirmule, Narendra; Khare, Ninad; Kalakuntla, Pranav; Zarkar, Rishi; Pawar, Sachi; Sheth, Smritie (Frontiers in Education, 2023)
Although vaccines are being developed and administered to people for more than a century, the understanding of the steps involved in vaccine development is a relatively new subject in the general public. During the current pandemic, there has been an explosion of non-validated news about COVID-19 and vaccines. To enhance the understanding of this critical societal science, there is an urgent need to teach these topics in the early education systems. Defining the essential subjects and courses for high school and developing syllabi for undergraduate courses in immunology and vaccinology can be difficult, as students choose diverse career options after their studies. To define these curricula, understanding the current level of awareness regarding vaccinology and immunology among students becomes essential. Thus, we have undertaken an exploratory survey of 650 high school and undergraduate college students in India and interviewed 8 students in United States on their awareness of processes of vaccine development. Our results confirmed our hypothesis that there is a very limited understanding of this topic amongst school-going students. In this article, we provide a brief overview of steps involved in the development of COVID-19 vaccines from a student's perspective and propose an outline to a course for teaching high school and undergraduate students. We recommend that this course should be interdisciplinary and a mix and match of majors and minors. It should train students with soft skills and prepare them for their careers in biomedical research.